2002
DOI: 10.1007/s00467-001-0792-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to intimin and Escherichia coli secreted proteins A and B in patients with enterohemorrhagic Escherichia coli infections

Abstract: Enterohemorrhagic Escherichia coli produce an attaching and effacing lesion upon adhering to the intestinal epithelium. Bacterial factors involved in this histopathology include the intimin adhesin and E. coli secreted proteins (Esps) A and B. In this study we investigated the serum antibody responses to recombinant E. coli O157:H7 intimin, EspA, and EspB by immunoblotting. Canadian patients with O157:H7 infection (n=10), Swedish patients with O157:H7 (n=21), non-O157 (n=18), or infection from which the seroty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 53 publications
1
21
0
1
Order By: Relevance
“…The immunogenicity of the LEE-encoded proteins studied here was also observed in patients infected with E. coli O157:H7 or other EHEC serotypes, as well as in their household contacts (13,18) or children with EPEC-associated diarrhea (23). Furthermore, several studies have shown that colostrum and milk from healthy women from both industrialized and developing countries contain IgA antibodies reactive to the LEE-encoded proteins (20,22,30,33).…”
Section: Discussionsupporting
confidence: 63%
“…The immunogenicity of the LEE-encoded proteins studied here was also observed in patients infected with E. coli O157:H7 or other EHEC serotypes, as well as in their household contacts (13,18) or children with EPEC-associated diarrhea (23). Furthermore, several studies have shown that colostrum and milk from healthy women from both industrialized and developing countries contain IgA antibodies reactive to the LEE-encoded proteins (20,22,30,33).…”
Section: Discussionsupporting
confidence: 63%
“…Pooled unadsorbed HUS convalescent-phase sera reacted strongly and specifically with E. coli XL1-Blue(pEB313) (35) and E. coli DH5␣(pCVD468, pREP4) (22), expressing His 6 -intimin-␥ and His 6 -EspA, respectively, in contrast to E. coli BL21(DE3) expressing recombinant Vibrio cholerae PilA, an irrelevant control protein (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…1B). Since both are reportedly expressed during human infection (22,29), as well as during in vitro growth (36), we anticipated reactivity with both might be eliminated by adsorption of the sera. We attribute the residual serum reactivity with intimin-␥ to relatively weak in vitro expression of this protein, which may be insufficient to adsorb away all of the anti-intimin-␥ antibodies generated in response Screening of an E. coli O157 genomic expression library.…”
Section: Resultsmentioning
confidence: 99%
“…Bands were detected at approximately 94 kDa and 37 kDa, corresponding to intimin and EspB, respectively (Fig. 4, lanes 1 and 2) (27). No bands were visualized for sera taken from mice in the PBS/EHEC group (n ϭ 2) before FIG.…”
Section: Resultsmentioning
confidence: 90%
“…EPEC or EHEC infections (11,27,31). It has been suggested that these antibodies could confer protection against subsequent EPEC infection.…”
mentioning
confidence: 99%